GOOGLE CLASSROOM AS AN EFFECTIVE TOOL OF SMART LEARNING AND MONITORING OF STUDENTS' KNOWLEDGE IN VOCATIONAL SCHOOLS - Гуревич, Роман Семенович; Шахіна, Ірина Юріївна; Подзигун, Олена Анатоліївна (Information technologies and learning tools, 2020)
The paper highlights the importance of monitoring students’ knowledge in the educational process organized on the basis of IT. The monitoring procedure in training enhances students’ knowledge. The results of this study show that the modernization of the monitoring in the educational process requires the use of modern computer equipment and means of communication. Electronic monitoring of students’ knowledge is the basis for obtaining an objective independent assessment of the level of students’ academic achievements (knowledge, intellectual and practical skills). The paper also presents the list of online services for creating broad-based tests, which include Google Forms, LEARNINGAPPS.ORG, PROPROFS, ClassMarker. Careful analysis of the learning forms allows us to present a way of organizing students’ training with the help of the Google platform, including the Google Classroom service (Learning Management System), which is essential for online learning and effective control of students’ knowledge of the subjects of their major. Unlike its predecessors, the Google Classroom as a separate learning management system allows teachers to use the integrated tools of the Google Apps package, such as Google Drive and Gmail. The main possibilities of using Google Classroom for the organization of Smart learning and monitoring of students’ knowledge are identified. The paper also presents detailed information on the possibilities for Google Classroom users (teachers, students, mentors, parents, administrators). The use of the Smart course, developed by means of the interactive services combined with the traditional methods of teaching information technologies, has made it possible to move the communication of students and teachers up to a new level – it is not limited only to a classroom. In the Google Classroom the educators can post tasks, send announcements, start discussions, and students can share materials, add comments on the course, communicate via e-mail. The information on the work done is constantly updated, which allows the educators to check the tasks quickly and monitor students’ knowledge. The article proves the effectiveness of using the Smart course on the basis of Google Classroom for the formation of information skills of students majoring in “Information and Software Processing Operator”.